2021
DOI: 10.1159/000518674
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Body Weight and Diverticular Disease

Abstract: <b><i>Background:</i></b> The worldwide proportion of overweight adults almost doubled from 22% in 1975 to 39% in 2016. Comparably, for the USA and Germany in 2016, the proportion was 68 and 56.8%, respectively. In Olmsted County, Minnesota, the prevalence of diverticulitis also doubled between 1980 and 2007, from 19 to 40%. Obesity substantially increases the risk of multiple gastrointestinal (GI) diseases and non-GI diseases. In a narrative review, we examined the evidence on whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 90 publications
0
9
0
1
Order By: Relevance
“…For example, studies had documented positive correlations between leiomyoma risk and plasma TG levels (Uimari et al, 2016) (Tonoyan et al, 2021) (Peshkova et al, 2020). Others had shown diverticular disease risk is positively associated with BMI, body fat percentage, and visceral fat area (Shih et al, 2022) (Freckelton et al, 2018) (Böhm, 2021). Similarly, kidney stones have been associated with the triglyceride-glucose (TyG) index (Qin et al, 2021), and atrial tachycardias have been associated with VLDL levels in metabolic syndrome patients (Lee et al, 2017) (Park & Lee, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies had documented positive correlations between leiomyoma risk and plasma TG levels (Uimari et al, 2016) (Tonoyan et al, 2021) (Peshkova et al, 2020). Others had shown diverticular disease risk is positively associated with BMI, body fat percentage, and visceral fat area (Shih et al, 2022) (Freckelton et al, 2018) (Böhm, 2021). Similarly, kidney stones have been associated with the triglyceride-glucose (TyG) index (Qin et al, 2021), and atrial tachycardias have been associated with VLDL levels in metabolic syndrome patients (Lee et al, 2017) (Park & Lee, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Schließlich konnte eine Analyse der Nurses Health Study an 1048 Patienten ebenfalls eine Assoziation zwischen Übergewicht und rezidivierenden Divertikulitiden nachweisen. Hierbei hatten Frauen mit einem BMI ≥ 30,0 kg/m 2 ein höheres Risiko für eine Rezidivdivertikulitis (HR 1,66), (95 % CI, 1,09–2,51; p = 0,002) im Vergleich zu Frauen mit einem BMI < 22,5 kg/m 2 , HR 1,44 (95 % CI, 1,16–1,79; p = < 0,001), 167 252 .…”
Section: Kapitel 3: Klinisches Erscheinungsbild (Definitionen) Natürl...unclassified
“…Reports are conflicting on the relationship between obesity and asymptomatic diverticulosis [10]. Some studies have shown that there is no relationship [11], while others have demonstrated an increased incidence of asymptomatic diverticulosis in obese patients [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…There is more clarity of evidence linking CDD to obesity. Obesity has been associated with progression from colonic diverticula to CDD, diverticular hemorrhage, diverticulitis, perforations, more severe or complicated disease, recurrent diverticulitis, and worse outcomes following surgical intervention [11,[13][14][15]. However, it is unclear if morbid obesity (MO) is associated with worse outcomes in patients admitted for CDD.…”
Section: Introductionmentioning
confidence: 99%